Inpatient Clinical Profile and Mortality Patterns at a Tertiary Referral Hospital in Indonesia: A Descriptive Study at RSUP Dr. M. Djamil Padang - Viora Antasya Viora; Dodi Vionanda Dodi; Alfitri Alfitri Alfitri (Frontiers on Healthcare Research, 2026)
Background: Hospital electronic medical records contain morbidity and mortality data that can be analyzed to provide a comprehensive picture of health profiles. However, most studies using inpatient data are limited in scope and do not integrate the distribution of diagnoses, mortality patterns, and case fatality rates into a single analytical framework. This study aimed to describe the characteristics of inpatients at Dr. M. Djamil General Hospital in Padang in 2025, including age distribution, gender, diagnosis patterns, mortality rates, and case fatality rates by diagnosis group. Methods: This study employed descriptive analysis of electronic medical record (EMR) data from Dr. M. Djamil General Hospital in Padang for 2025, involving a total of 38,539 inpatients. The variables analyzed were age group, gender, and primary diagnosis. Data were presented in tables and bar charts. Results: Throughout 2025, there were 38,539 inpatients, with the highest number in the 56–60 age group. Males dominated inpatient admissions in nearly all age groups, except for the 21–50 age group, which was dominated by females because of pregnancy complications and gynecological cancers. Of all patients, 4,517 (8.5%) died, with the highest mortality rate occurring in the 61–65 age group. The highest case fatality rates (CFRs) were recorded for diseases of the respiratory system (29.2%); endocrine, nutritional, and metabolic diseases (23.5%); and perinatal conditions (21.0%), surpassing neoplasms and diseases of the circulatory system, which actually recorded the largest absolute numbers of deaths. Disease patterns varied by age group; most notably, admissions among women aged 21–50 were dominated by pregnancy-related conditions and gynecological cancers, whereas those among men over 51 were dominated by diseases of the circulatory system. Conclusion: The patterns of hospital admissions and deaths at Dr. M. Djamil General Hospital in Padang indicated that men and women faced different disease risks at each stage of life. These findings indicate that prevention programs and hospital healthcare services will need to be designed differently according to gender and age group to ensure greater effectiveness.